CMAS-corrosion-resistant high-entropy ceramic material and preparation method thereof
By using (YGDERDY) 2 (1-X) YB2XZR2O7 high-entropy ceramic material, a single-phase fluorite structure is formed and a dense reaction layer is generated. Corrosion performance and structural stability.
Patent Information
- Application Number
- CN202411372324.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Existing YSZ ceramic materials are prone to phase transformation and CMAS corrosion in high temperature environments, resulting in coating failure and peeling, making it difficult to meet the needs of high-temperature structural stability and corrosion resistance.
(YGDERDY) 2 (1-X) YB2XZR2O7 high-entropy ceramic material, it forms a single-phase fluorite structure at high temperature, and the density reaction layer is generated by reacting the reaction with CA and SI elements through rare earth ions to block the further erosion of CMAS.
The high -entropy ceramic material shows a more dense reaction layer under CMAS corroded at 1300 ° C, significantly improved the corrosion performance and structural stability of CMAS, and extend the service life of the coating.
Smart Images

Figure CN119330711A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal barrier coatings, and in particular to a high-entropy ceramic material resistant to CMAS corrosion and a preparation method thereof. Background Art
[0002] Thermal barrier coatings (TBCs) are key technologies for improving the reliability and service life of aircraft engine turbine blades. Currently, the widely used thermal barrier coating material 7-8YSZ ceramic material has the advantages of high melting point, low thermal conductivity and thermal expansion coefficient similar to that of the alloy substrate. However, with the development of aircraft engines and the increase in service temperature, YSZ also has many difficult to solve problems. At around 1170℃ and 2370℃, ZrO2 will undergo a phase transition from monoclinic phase (m-ZrO2) to tetragonal phase (t-ZrO2) and cubic phase (c-ZrO2). During the cooling process after the temperature drops, the t-ZrO2 in the YSZ will undergo a reverse phase transition to m-ZrO2. The volume change caused by the phase transition in this process is about 4%. Due to the volume change during the thermal cycle, the ceramic layer fails and eventually causes the coating to peel off. In addition, the YSZ coating will also suffer from molten CMAS corrosion in a high temperature environment. CMAS is deposited on the engine blades after high-temperature melting, penetrates into the interior of the blade surface coating through pores and cracks, reacts with YSZ, and promotes the metastable phase (t'-ZrO2) in YSZ to gradually transform into t-ZrO2 phase and c-ZrO2 phase. The phase transition causes volume expansion, and after CMAS penetrates into the gaps in the columnar structure of the YSZ coating, the strain tolerance of the coating is reduced, resulting in a reduced coating service life and an accelerated peeling rate. Therefore, it is necessary to develop new thermal barrier coating materials with high-temperature structural stability and high-temperature corrosion resistance. Summary of the invention
[0003] In view of the shortcomings of the prior art, the first object of the present invention is to provide a high entropy ceramic material resistant to CMAS corrosion. The high entropy ceramic material provided by the present invention has excellent high temperature stability and CMAS corrosion resistance.
[0004] The second object of the present invention is to provide a method for preparing a high entropy ceramic material resistant to CMAS corrosion.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a high entropy ceramic material resistant to CMAS corrosion, wherein the chemical formula of the high entropy ceramic material is (YGdErDy) 2(1-x) Yb 2x Zr2O7, wherein 0≤x<1, preferably 0.2≤x<0.8, and further preferably 0.4≤x<0.8.
[0007] After being corroded by CMAS, the high entropy ceramic material provided by the present invention contains a variety of rare earth ions with different radii. They react with Ca and Si elements to form needle-shaped apatite, and zirconate decomposes to produce ZrO2. Elements with smaller rare earth ion radius tend to form larger spherical ZrO2, and elements with larger rare earth ion radius tend to form needle-shaped apatite more easily. As the corrosion time increases, the two products form a dense reaction layer to block further corrosion of CMAS. Among them, Yb2O3 has a smaller ion radius and good compatibility, which is conducive to phase stability. As the Yb2O3 content increases and the corrosion time increases, Yb 3+ The ions enter ZrO2, forming more and larger spherical ZrO2 with closer contact, making the reaction layer denser and preventing further erosion of CMAS.
[0008] In a preferred embodiment, the high entropy ceramic material resistant to CMAS corrosion is a single-phase fluorite structure. The high entropy ceramic material formed by the chemical formula of the present invention is a single-phase fluorite structure, which is stable and will not undergo phase change when corroded. Based on this, compared with the two-phase structure of YSZ ceramics, phase change will occur during corrosion, and it also has better CMAS corrosion resistance.
[0009] The present invention also provides a method for preparing a high-entropy ceramic material resistant to CMAS corrosion. The method comprises the following steps: preparing various oxide raw materials according to the chemical composition of the high-entropy ceramic material, subjecting the oxide raw materials to a first ball milling to obtain a mixed powder, pre-firing the mixed powder to obtain a pre-firing powder, subjecting the pre-firing powder to a second ball milling to obtain a pre-firing ball-milled powder, granulating the pre-firing ball-milled powder to obtain a granulated powder, pressing the granulated powder to obtain a green body, and sintering the green body to obtain the high-entropy ceramic material.
[0010] The technical solution of the present invention is simple and controllable, with low cost, and adopts a traditional solid phase method, and a high entropy ceramic material resistant to CMAS corrosion can be obtained through one pre-firing and one sintering.
[0011] In a preferred solution, each oxide raw material is first calcined at 700-800° C. for 2-3 hours. In actual operation, various oxide raw materials are placed in different zirconia crucibles and calcined to remove moisture and organic impurities in the raw materials.
[0012] A preferred solution is to prepare Y2O3 powder, Gd2O3 powder, Er2O3 powder, Dy2O3 powder, Yb2O3 powder and ZrO2 powder according to the chemical composition of the high entropy ceramic material. The particle sizes of the Y2O3 powder, Gd2O3 powder, Er2O3 powder, Dy2O3 powder, Yb2O3 powder and ZrO2 powder are all 50-100nm, and the purity is ≥99.9%.
[0013] By controlling the particle size of each raw material powder within the above range, the final high entropy ceramic material has the best density and the most uniform composition. Within this particle size range, there are many structural defects generated during the preparation process, and the sintering activity is high, which can promote sintering and densification.
[0014] In a preferred embodiment, the rotation speed of the first ball milling is 300-350 rpm, and the time of the first ball milling is 10-12 h.
[0015] In a preferred embodiment, the first ball milling is wet ball milling, and the ball milling medium is anhydrous ethanol.
[0016] In a preferred embodiment, the first ball milling is followed by drying, and then grinding to obtain a mixed powder. The drying temperature is 70-90° C. and the drying time is 6-10 h.
[0017] In a preferred embodiment, the pre-sintering temperature is 1500-1550°C and the time is 6-10 hours. The raw materials are reacted to generate the target product by pre-sintering, but the pre-sintering temperature cannot be too high. If the temperature is too high and the holding time is too long, the activity of the fired powder will be worse, which is not conducive to subsequent sintering. If the pre-sintering temperature is too low, the reaction will not be sufficient.
[0018] In a preferred embodiment, the second ball milling speed is 450-500 rpm and the second ball milling time is 10-12 hours. In the present invention, the second ball milling speed has a great influence on the density of the final ceramic material. If the speed is too low, the grinding is insufficient, the powder particle size is large, which is not conducive to subsequent sintering and the ceramic density decreases; if the ball milling speed is too high, it will cause pollution to the powder.
[0019] In a preferred embodiment, the second ball milling is wet ball milling, and the ball milling medium is anhydrous ethanol.
[0020] In a preferred embodiment, after the second ball milling is completed, drying is performed to obtain the pre-calcined ball milled powder, and the drying temperature is 70-90° C. and the drying time is 6-10 hours.
[0021] In a preferred embodiment, the granulation process is as follows: polyvinyl alcohol (PVA) is added to the pre-burnt ball mill powder, followed by grinding, and then sifting through a 300-500 mesh sieve to obtain the granulated powder. The amount of PVA added is 6-8% of the mass of the pre-burnt ball mill powder.
[0022] When granulating, the amount of PVA added is controlled within the above range, which can not only allow the pre-burned ball mill powder to be fully and evenly ground, but also enable it to be well shaped. If too little PVA is added, the adhesion is insufficient, affecting the briquetting; if too much PVA is added, the grinding will be uneven.
[0023] In a preferred embodiment, the granulated powder is pressed and molded by preforming by molding, and then the green body is obtained by cold isostatic pressing. The preforming pressure is 10-20 MPa, and the holding time of the preforming is 5-7 min. The cold isostatic pressing pressure is 200-220 MPa, and the holding time of the cold isostatic pressing is 5-7 min.
[0024] In the actual operation, the powder is preformed by using a tablet press at a pressure of 20 MPa for 5-7 minutes to obtain green blanks of different shapes. Then, the preformed green blanks are pressed by cold isostatic pressing at a pressure of 200-220 MPa for 5-7 minutes to obtain the final green blanks required for the experiment.
[0025] In a preferred embodiment, the sintering temperature is 1550-1700° C. and the sintering time is 10-20 hours.
[0026] Further preferably, the sintering process is: heating to 600-700°C at a heating rate of 5-10°C / min, keeping warm for 2-3h, then heating to 1550-1700°C at a heating rate of 5-10°C / min, keeping warm for 10-20h, cooling to 700-800°C at a cooling rate of 1-2°C / min after keeping warm, and then cooling with the furnace.
[0027] In a further preferred sintering process, the temperature is first raised from room temperature to 600-700°C. At this stage, the shape of the particles remains basically unchanged, the entire sintered body does not shrink, and the density increases very little. The temperature is kept at 600-700°C for 2-3 hours to remove PVA. Then it is raised to 1550-1700°C and kept for 10-20 hours. The grains grow, and the materials on the grain boundaries diffuse and fill the pores, gradually densifying. After the insulation is completed, the temperature is reduced to 700-800°C at a cooling rate of 1-2°C / min to avoid cooling too fast, which causes a large temperature difference between the inside and outside of the ceramic, resulting in large thermal stress and cracking of the ceramic. During the entire sintering process, the sintering insulation temperature needs to be effectively controlled. If the sintering temperature is too high, the grains will coarsen and grow rapidly, which is not conducive to the removal of pores, and will cause a large number of residual pores to limit the density of the material. And excessive grain growth will reduce the mechanical properties of the ceramic.
[0028] Beneficial effects:
[0029] The present invention is a new type of thermal barrier coating material, which is designed by high entropy rare earth zirconate (YGdErDy) 2(1-x) Yb 2xZr2O7 high entropy ceramic material. After high-temperature sintering, this material has a single-phase fluorite structure. Compared with YSZ, it has higher structural stability, is suitable for higher temperature service conditions, and is conducive to improving the service life of thermal barrier coatings. At the same time, under CMAS corrosion at 1300°C, the reaction layer of this material is much smaller than that of YSZ, and the reaction layer is dense, which is conducive to preventing further erosion of CMAS. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 XRD diffraction patterns of ceramic samples obtained in 4 embodiments;
[0031] Figure 2 The morphology of the ceramic samples obtained in 4 examples are as follows: (a) Example 1; (b) Example 2; (c) Example 3; (d) Example 4;
[0032] Figure 3 Schematic diagrams of cross sections of the examples and comparative examples after CMAS corrosion at 1300° C.: (a) Example 1 is corroded for 1 h; (b) Example 2 is corroded for 1 h; (c) Example 3 is corroded for 1 h; (d) Example 4 is corroded for 1 h; (e) Comparative Example 1 is corroded for 1 h;
[0033] Figure 4 Schematic diagram of the cross-sections of the examples and comparative examples after CMAS corrosion at 1300°C: (a) Example 1 is corroded for 50 h; (b) Example 2 is corroded for 50 h; (c) Example 3 is corroded for 50 h; (d) Example 4 is corroded for 50 h; (e) Comparative example 1 is corroded for 50 h. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below in combination with embodiments and comparative examples. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] The following test methods were used in each embodiment and comparative example:
[0036] Anti-CMAS performance test:
[0037] The powders of CaO, MgO, Al2O3 and SiO2 were evenly mixed by ball milling at a molar percentage of 33:9:13:45, and placed in a box-type resistance furnace for constant temperature heating for 8 hours at 1300℃. After cooling in the furnace, the formed glassy CMAS was ground and sieved to a powder with a particle size of about 30μm. CMAS was sieved at a concentration of 20mg / cm 2The coating amount was uniformly coated on the surface of the prepared ceramic blocks with different compositions, and then placed in a resistance furnace and corroded at 1300℃ for different time periods. The samples were then cooled in the furnace, and the cross-sections of the corroded samples were made into metallographic samples. The corrosion area of CMAS on the blocks was characterized by a scanning electron microscope (SEM) with an energy dispersive spectrometer (EDS), and the penetration depth of CMAS in the ceramics was compared.
[0038] Example 1
[0039] (Y 0.25 G 0.25 Er 0.25 Dy 0.25 Preparation of 2Zr2O7 Ceramics (x=0)
[0040] (1) Various oxide raw materials are placed in different zirconia crucibles and calcined at 700-800°C for 2 hours to remove moisture and organic impurities in the raw materials.
[0041] (2) According to the molar ratio of Y2O3, Gd2O3, Er2O3, Dy2O3, Yb2O3, and ZrO2 of 1:1:1:1:0:8, appropriate amounts of powders were weighed and poured into a zirconia ball mill jar in sequence, and appropriate amounts of zirconia balls and anhydrous ethanol were added. Then, the first ball milling mixing was carried out at a speed of 300 rpm for 10 h.
[0042] (3) The mixed slurry is placed in a drying oven and dried at 80° C. for 10 h. After drying, the mixed slurry is ground to obtain a mixed powder. The mixed powder is pre-calcined at a pre-calcination temperature of 1550° C. for 10 h to obtain a pre-calcined powder.
[0043] (4) The calcined powder was mixed with anhydrous ethanol and ball-milled for a second time at a speed of 500 rpm for 10 h, and then dried at 80° C. for 10 h, and then passed through a 300-mesh sieve, and then 8% PVA was added to grind and granulate.
[0044] (5) The powder is preformed by a tablet press at a pressure of 20 MPa for 5-7 minutes to obtain green blanks of different shapes. Then, the preformed green blanks are pressed by cold isostatic pressing at a pressure of 200-220 MPa for 5-7 minutes to obtain the final green blanks required for the experiment.
[0045] (6) Finally, the second sintering was carried out at a temperature of 1550°C for 20 hours. The sintering process includes: heating to 700°C at a rate of 10°C / min and keeping at that temperature for 2 hours to remove PVA. Then, the temperature was raised to 1550°C at a rate of 5°C / min and kept at that temperature for 20 hours. After keeping at that temperature, the temperature was lowered to 800°C at a rate of 1°C / min to prevent the sample from cracking due to excessive cooling. Then, the sample was cooled in the furnace to obtain a ceramic block.
[0046] At 20mg / cm 2 The CMAS powder is weighed in an amount and evenly coated on the surface of the obtained ceramic block, which is then placed in a high-temperature resistance furnace for a corrosion test at a corrosion temperature of 1300°C.
[0047] The method prepared (Y 0.25 G 0.25 Er 0.25 Dy 0.25 The phase structure of 2Zr2O7 ceramic is single-phase fluorite structure, with a density of 98.1%. The depth of the reaction layer after corrosion for 1 hour is 22.4μm, and the depth of the reaction layer after corrosion for 50 hours is 60.2μm.
[0048] Example 2
[0049] (Y 0.2 G 0.2 Er 0.2 Dy 0.2 Yb 0.2 Preparation of 2Zr2O7 Ceramics (x=0.2)
[0050] Weigh appropriate amounts of powders according to the molar ratio of Y2O3, Gd2O3, Er2O3, Dy2O3, Yb2O3 and ZrO2 of 1:1:1:1:1:10, and prepare ceramics using the preparation method described in Example 1.
[0051] At 20mg / cm 2 The CMAS powder is weighed in an amount and evenly coated on the surface of the obtained ceramic block, which is then placed in a high-temperature resistance furnace for a corrosion test at a corrosion temperature of 1300°C.
[0052] The method prepared (Y 0.2 G 0.2 Er 0.2 Dy 0.2 Yb 0.2 The phase structure of 2Zr2O7 ceramic is single-phase fluorite structure with a density of 98.3%. The depth of the reaction layer after corrosion for 1 hour is 20μm, and the depth of the reaction layer after corrosion for 50 hours is 54.7μm.
[0053] Example 3
[0054] (Y 0.15 G 0.15 Er 0.15 Dy 0.15 Yb 0.4 Preparation of 2Zr2O7 Ceramics (x=0.4)
[0055] Weigh appropriate amounts of powders according to the molar ratio of Y2O3, Gd2O3, Er2O3, Dy2O3, Yb2O3 and ZrO2 of 3:3:3:3:8:40, and prepare ceramics using the preparation method described in Example 1.
[0056] At 20mg / cm 2 The CMAS powder is weighed in an amount and evenly coated on the surface of the obtained ceramic block, which is then placed in a high-temperature resistance furnace for a corrosion test at a corrosion temperature of 1300°C.
[0057] The method prepared (Y 0.15 G 0.15 Er 0.15 Dy 0.15 Yb 0.4 The phase structure of 2Zr2O7 ceramic is single-phase fluorite structure with a density of 97.8%. The depth of the reaction layer after corrosion for 1 hour is 18.2μm, and the depth of the reaction layer after corrosion for 50 hours is 41.9μm.
[0058] Example 4
[0059] (Y 0.05 G 0.05 Er 0.05 Dy 0.05 Yb 0.8 Preparation of 2Zr2O7 Ceramics (x=0.8)
[0060] Weigh appropriate amounts of powders according to the molar ratio of Y2O3, Gd2O3, Er2O3, Dy2O3, Yb2O3 and ZrO2 of 1:1:1:1:16:40, and prepare ceramics using the preparation method described in Example 1.
[0061] At 20mg / cm 2 The CMAS powder is weighed in an amount and evenly coated on the surface of the obtained ceramic block, which is then placed in a high-temperature resistance furnace for a corrosion test at a corrosion temperature of 1300°C.
[0062] The method prepared (Y 0.05 G 0.05 Er 0.05 Dy 0.05 Yb 0.8 The phase structure of 2Zr2O7 ceramic is single-phase fluorite structure with a density of 97.9%. The depth of the reaction layer after corrosion for 1 hour is 16.7μm, and the depth of the reaction layer after corrosion for 50 hours is 30.1μm.
[0063] Comparative Example 1
[0064] Appropriate amounts of Y2O3 and ZrO2 powders were weighed in a mass ratio of 7%:93%, and ceramic YSZ was prepared using the preparation method described in Example 1.
[0065] At 20mg / cm 2 The CMAS powder is weighed in an amount and evenly coated on the surface of the obtained ceramic block, which is then placed in a high-temperature resistance furnace for a corrosion test at a corrosion temperature of 1300°C.
[0066] The YSZ ceramic prepared by the above method has a dual-phase structure, a density of 92.3%, a reaction layer depth of 714.2 μm after corrosion for 1 h, and a reaction layer depth of 922.1 μm after corrosion for 50 h.
[0067] Comparative Example 2
[0068] Only the second ball milling speed was changed to 300 rpm, and other conditions were consistent with Example 1. The fired ceramic surface had inconsistent color, uneven composition, and cracks on the surface.
[0069] Comparative Example 3
[0070] Only the cooling rate during sintering was changed, and the ceramic was allowed to cool directly with the furnace after the heat preservation. Other conditions were consistent with those in Example 1, and the fired ceramic cracked when touched.
[0071] Performance test analysis
[0072] Depend on Figure 1 It can be seen that the prepared ceramic materials all have a single-phase fluorite structure, are structurally stable at 1550°C, and have good structural stability.
[0073] Depend on Figure 2 It can be seen that the ceramic material provided in the embodiment has a dense surface and fewer pores.
[0074] Depend on Figure 3 and Figure 4 It can be seen that the reaction layer of this ceramic material is much smaller than that of YSZ. After the high entropy ceramic is corroded by CMAS, the rare earth ions in it react with Ca and Si elements to form needle-shaped apatite, and zirconate decomposes to produce ZrO2. With the increase of Yb2O3 content and the extension of corrosion time, more and larger spherical ZrO2 is generated, making the reaction layer denser and blocking further erosion of CMAS. Therefore, this ceramic material has stronger resistance to CMAS corrosion than YSZ.
Claims
1. A high entropy ceramic material resistant to CMAS corrosion, characterized in that: The chemical formula of the high entropy ceramic material is (YGdErDy) 2(1-x) Yb 2x Zr2O7, where 0≤x<1.
2. A high entropy ceramic material resistant to CMAS corrosion according to claim 1, characterized in that: The high-entropy ceramic material resistant to CMAS corrosion is a single-phase fluorite structure.
3. The method for preparing a high entropy ceramic material resistant to CMAS corrosion according to claim 1 or 2, characterized in that: The oxide raw materials are prepared according to the chemical composition of the high entropy ceramic material, the oxide raw materials are subjected to a first ball milling to obtain a mixed powder, the mixed powder is pre-fired to obtain a pre-fired powder, the pre-fired powder is subjected to a second ball milling to obtain a pre-fired ball-milled powder, the pre-fired ball-milled powder is granulated to obtain a granulated powder, the granulated powder is pressed into a shape to obtain a green body, and the green body is sintered to obtain a high entropy ceramic material.
4. The method for preparing a high-entropy ceramic material resistant to CMAS corrosion according to claim 3, characterized in that: Each oxide raw material is first calcined at 700-800°C for 2-3h; According to the chemical composition of high entropy ceramic materials, Y2O3 powder, Gd2O3 powder, Er2O3 powder, Dy2O3 powder, Yb2O3 powder and ZrO2 powder are prepared. The particle sizes of the Y2O3 powder, Gd2O3 powder, Er2O3 powder, Dy2O3 powder, Yb2O3 powder and ZrO2 powder are all 50-100nm, and the purity is all ≥99.9%.
5. The method for preparing a high-entropy ceramic material resistant to CMAS corrosion according to claim 3, characterized in that: The rotation speed of the first ball milling is 300-350rpm, and the time of the first ball milling is 10-12h; After the first ball milling is completed, the mixture is dried and then ground to obtain a mixed powder. The drying temperature is 70-90° C. and the drying time is 6-10 hours.
6. The method for preparing a high-entropy ceramic material resistant to CMAS corrosion according to claim 3, characterized in that: The pre-burning temperature is 1500-1550° C. and the pre-burning time is 6-10 hours.
7. The method for preparing a high-entropy ceramic material resistant to CMAS corrosion according to claim 3, characterized in that: The second ball milling speed is 450-500 rpm, and the second ball milling time is 10-12 h; After the second ball milling is completed, drying is performed to obtain pre-calcined ball milled powder, and the drying temperature is 70-90° C. and the drying time is 6-10 hours.
8. The method for preparing a high-entropy ceramic material resistant to CMAS corrosion according to claim 3, characterized in that: The granulation process is as follows: PVA is added to the pre-burned ball mill powder, and then ground, and then sieved through a 300-500 mesh sieve to obtain the granulated powder, wherein the amount of PVA added is 6-8% of the mass of the pre-burned ball mill powder; The process of pressing and molding the granulated powder is to first perform pre-molding by molding, and then obtain a green body by cold isostatic pressing. The pre-molding pressure is 10-20 MPa, and the holding time of the pre-molding is 5-7 minutes. The cold isostatic pressing pressure is 200-220 MPa, and the holding time of the cold isostatic pressing is 5-7 minutes.
9. The method for preparing a high-entropy ceramic material resistant to CMAS corrosion according to claim 3, characterized in that: The sintering temperature is 1550-1700° C., and the sintering time is 10-20 hours.
10. The method for preparing a high entropy ceramic material resistant to CMAS corrosion according to claim 9, characterized in that: The sintering process is as follows: heating to 600-700°C at a heating rate of 5-10°C / min, keeping warm for 2-3h, then heating to 1550-1700°C at a heating rate of 5-10°C / min, keeping warm for 10-20h, cooling to 700-800°C at a cooling rate of 1-2°C / min after the insulation is completed, and then cooling with the furnace.
Citation Information
Patent Citations
High-entropy rare earth hafnate ceramic material and preparation method thereof
CN110606740A
High-entropy ceramic material resistant to CMAS corrosion and preparation method and application thereof
CN112341197A
A2B2O7 type high-entropy ceramic powder, gamma ray shielding composite coating and preparation method
CN115368130A
Thermal barrier coating material having high fracture toughness, CMAS corrosion resistance and ultra-high-temperature sintering resistance and preparation and application thereof, and thermal barrier coating
WO2024093144A1
Cited By
Defect-fluorite-structured high-entropy ceramic material resistant to cmas corrosion and preparation method thereof
CN122705298A